2013
DOI: 10.1007/s10557-013-6439-z
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Effect of Nitrates on Exercise Stress Test Results in Patients with Microvascular Angina

Abstract: Short-acting nitrates improve EST results in CAD, but not in MVA patients. In MVA patients a lower nitrate-dependent coronary microvascular dilation may contribute to the lack of effects of nitrates on EST results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(45 citation statements)
references
References 23 publications
0
42
0
3
Order By: Relevance
“…If this does not lead to improvement of symptoms additional antianginal drugs should be given (see below). Studies on long acting nitrates have shown no positive effect and are thus not recommended in CMD patients [20]. Although in rare cases they may be effective.…”
Section: Recommendations For Treatmentmentioning
confidence: 99%
“…If this does not lead to improvement of symptoms additional antianginal drugs should be given (see below). Studies on long acting nitrates have shown no positive effect and are thus not recommended in CMD patients [20]. Although in rare cases they may be effective.…”
Section: Recommendations For Treatmentmentioning
confidence: 99%
“…Among the traditional anti-ischemic drugs, which remain the first-line approach of treatment, long-acting nitrates were evaluated in only 1 single small study, which showed no significant effects in the control of symptoms [5]. Furthermore, the clinical utility of long-acting nitrates in MVA patients can also be questioned by the inconstant efficacy of short-acting nitrates in fully relieving angina attacks [16,17] as well as by the lack of significant effects on ischemic ST segment changes induced by the EST [18,19]. …”
Section: Discussionmentioning
confidence: 99%
“…[7, 10, 11] Clinical features that may aid in the diagnosis include angina at rest, angina that lingers after cessation of exercise, and angina that does not respond or worsens with short-acting nitrates during exercise or stress testing. [11, 14, 32, 33] In the setting of exertional angina or angina equivalent with normal coronary angiography and no epicardial coronary artery spasm, abnormal myocardial blood flow and/or coronary blood flow are strongly suggestive of microvascular angina.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…They have been associated with improvements in both symptoms and coronary flow reserve in this population. [85] Nitrates are commonly used to relieve angina in coronary artery disease, but they may be less beneficial in microvascular angina[33] as they exert their vasodilatory effects primarily in vessels larger than 200 micrometers. [86] Ranolazine is an alternative anti-anginal agent that has been shown to improve both angina symptoms and coronary flow reserve in microvascular angina.…”
Section: Therapeutic Strategiesmentioning
confidence: 99%